DAMPAK TEROR BOM TERHADAP KINERJA BURSA SAHAM INDONESIA - Wahab, Zusma Widawaty A.; Elvina, Elvina (JURNAL FAIRNESS, 2014)
The objective of this research is to find empirical evidence of the impact of bombing in several places in Indonesia on the Indonesian capital market performance. This study explores event study method and selects Indonesian public listed companies that classified as LQ-45 companies as a sample. This study found there is no significant abnormal return change around bombing period. However, this study found there is an increasing of trading activity of Indonesian capital market around those bombing period